PROSES EVALUASI KOLEKSI BAHAN PUSTAKA DI PERPUSTAKAAN KHUSUS BALAI PELATIHAN PERTANIAN (BAPELTAN) LAMPUNG - Dwinta, Anisa; Arnila Purnamayanti; Sugiyanta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2025)
The Lampung Agricultural Training Center Library supports the vision and mission of its parent institution to establish policies in managing the library. The special library standard explains that the special library policy is integrated or synergistic with the parent institution's policy. This writing method uses a descriptive quantitative approach, where this method is carried out using observation techniques, interviews with librarians, as well as documentation that supports this writing in order to obtain results that are appropriate to the conditions at the Lampung Agricultural Training Center Special Library. The result of this writing is that the Lampung Agricultural Training Center Special Library has a collection consisting of books, CD-ROM/VCD, newspapers, agricultural magazines andfiction books. 95% of the collection focuses on agriculture. Total: The collection has 1,162 titles with 1,947 copies. Evaluation of the library at the point of vision and mission that supports the duties of the parent institution, number of collections, procurement of collections, preservation of library collections, age of collections, facilities and infrastructure, re-enumeration of library collections, and organization of library materials in accordance with the regulations of the Republic of Indonesia Standards concerning National Standards for Special Library ( SNPK). The obstacles that occur in the process of evaluating library material collections in the special library at the Lampung agricultural training center are the lack of human resources so that it takes quite a long time for the process of evaluating library materials and the presenceof librarians who do not have a library expert background.